ANALYSIS OF THE EXPECTATION-CONFIRMATION MODEL IN CONTINUANCE INTENTION TO USE THE MAXIM APPLICATION - Hamid, Nisrina; Conny, Conny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The online transportation application has emerged as a practical solution for the public in the era of globalization and digitalization. MAXIM, one of the rapidly growing online transportation applications in Kendari city, serves as a focal point in this study. The research aims to analyze the impact of the Expectation Confirmation Model (ECM) on the intention to continue using the MAXIM application. With a sample size of 140 respondents chosen through purposive sampling, data was collected via a questionnaire measuring perceived usefulness, confirmation, habit, and intention to continue. The data analysis employed Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings reveal that confirmation significantly and positively influences perceived usefulness and habit, demonstrating a strong correlation. Conversely, while the impact of confirmation on satisfaction remains positive, it is relatively weak. Additionally, perceived usefulness and habit exhibit significant positive effects on the intention to continue usage. Despite satisfaction's positive influence on continuation intention, its impact is comparatively weak. User experience may serve as a viable variable for future research endeavors.